Rheological properties of isotactic polypropylene/kaolin composites - Maiti, S.N.; Lopez, B.H.; Ibrahim, Mohd Nordin (Informa UK Limited, 2002)
Rheological properties of isotactic polypropylene/kaolin composites have been evaluated at kaolin concentrations 0-17.4 vol% at 493K. The systems obeyed power-law model in shear stress-shear rate variations and were shear thinning, which increased with kaolin content. Apparent melt viscosity decreased up to 5% kaolin and increased with further increase in kaolin concentration. First normal stress difference increased up to 5 vol% kaolin and decreased beyond this kaolin content. Use of a titanate coupling agent modified the rheological properties through an enhanced bonding between the filler and the polymer.